Vectorial capacity and TEP1 genotypes of Anopheles gambiae sensu lato mosquitoes on the Kenyan coast - Bartilol, B; Omuoyo, D; Karisa, J; Ominde, K; Mbogo, C; Mwangangi, J; Maia, M; Rono, MK (BioMed Central, 2022)
Background Malaria remains one of the most important infectious diseases in sub-Saharan Africa, responsible for approximately 228 million cases and 602,000 deaths in 2020. In this region, malaria transmission is driven mainly by mosquitoes of the Anopheles gambiae and, more recently, Anopheles funestus complex. The gains made in malaria control are threatened by insecticide resistance and behavioural plasticity among these vectors. This, therefore, calls for the development of alternative approaches such as malaria transmission-blocking vaccines or gene drive systems. The thioester-containing protein 1 (TEP1) gene, which mediates the killing of Plasmodium falciparum in the mosquito midgut, has recently been identified as a promising target for gene drive systems. Here we investigated the frequency and distribution of TEP1 alleles in wild-caught malaria vectors on the Kenyan coast. Methods Mosquitoes were collected using CDC light traps both indoors and outdoors from 20 houses in Garithe village, along the Kenyan coast. The mosquitoes were dissected, and the different parts were used to determine their species, blood meal source, and sporozoite status. The data were analysed and visualised using the R (v 4.0.1) and STATA (v 17.0). Results A total of 18,802 mosquitoes were collected, consisting of 77.8% (n = 14,631) Culex spp., 21.4% (n = 4026) An. gambiae sensu lato, 0.4% (n = 67) An. funestus, and 0.4% (n = 78) other Anopheles (An. coustani, An. pharoensis, and An. pretoriensis). Mosquitoes collected were predominantly exophilic, with the outdoor catches being higher across all the species: Culex spp. 93% (IRR = 11.6, 95% Cl [5.9–22.9] P < 0.001), An. gambiae s.l. 92% (IRR = 7.2, 95% Cl [3.6–14.5]; P < 0.001), An. funestus 91% (IRR = 10.3, 95% Cl [3.3–32.3]; P < 0.001). A subset of randomly selected An. gambiae s.l. (n = 518) was identified by polymerase chain reaction (PCR), among which 77.2% were An. merus, 22% were An. arabiensis, and the rest were not identified. We were also keen on identifying and describing the TEP1 genotypes of these mosquitoes, especially the *R3/R3 allele that was identified recently in the study area. We identified the following genotypes among An. merus: *R2/R2, *R3/R3, *R3/S2, *S1/S1, and *S2/S2. Among An. arabiensis, we identified *R2/R2, *S1/S1, and *S2/S2. Tests on haplotype diversity showed that the most diverse allele was TEP1*S1, followed by TEP1*R2. Tajima’s D values were positive for TEP1*S1, indicating that there is a balancing selection, negative for TEP1*R2, indicating there is a recent selective sweep, and as for TEP1*R3, there was no evidence of selection. Phylogenetic analysis showed two distinct clades: refractory and susceptible alleles. Conclusions We find that the malaria vectors An. gambiae s.l. and An. funestus are predominantly exophilic. TEP1 genotyping for An. merus revealed five allelic combinations, namely *R2/R2, *R3/R3, *R3/S2, *S1/S1 and *S2/S2, while in An. arabiensis we only identified three allelic combinations: *R2/R2, *S1/S1, and *S2/S2. The TEP1*R3 allele was restricted to only An. merus among these sympatric mosquito species, and we find that there is no evidence of recombination or selection in this allele.